Mithun (Bos Frontalis): A Forest-Based Food Animal Of The Eastern Hima layas - Kumar, Harshit; Choudhary, Jagdish; Chotso, Kuluve; Moon Mech, Moon; Sunitibala Devi, L; Stephen Hanah, Sapunii; Kumar Chamuah, Jayanta; Patil Shivanagowda, Girish (Journal of Meat Science, 2026)
Mithun (Bos frontalis) is a domesticated bovine native to the Eastern Himalayas,  traditionally managed under forest-based systems and primarily utilized  for meat by indigenous communities. Despite its cultural and nutritional  importance, Mithun remains underrepresented in formal meat production  research and development programs. This review critically evaluates existing  literature with emphasis on meat production potential, carcass characteristics,  meat quality attributes and biological determinants influencing growth and  meat yield. Evidence from studies encompassing nutrition, growth physiology,  genetics, reproduction and health management indicates that Mithun exhibits  favorable meat composition, efficient utilization of fibrous forest biomass and  inherent adaptability to low-input production environments. Available data  also suggest the presence of genetic traits associated with disease tolerance and  environmental resilience, which may indirectly influence meat productivity.  Advances in reproductive biotechnologies, genomic characterization and  microbiome research offer new opportunities for genetic improvement and  conservation of meat-related traits. However, habitat degradation, genetic  erosion, limited performance recording and lack of organized slaughter  and processing infrastructure constrain its integration into structured meat  value chains. The review highlights the need for targeted research on growth  performance, carcass evaluation and meat quality parameters, coupled with  conservation-oriented breeding and value-chain development. Positioning  Mithun as a niche forest-based meat animal may support sustainable meat  production and livelihood enhancement in the Eastern Himalayan region.
Keywords: mithun; meat quality; carcass traits; sustainable meat production